2015
DOI: 10.1177/0308022615575670
|View full text |Cite
|
Sign up to set email alerts
|

The association between impulsivity and sensory processing patterns in healthy adults

Abstract: Introduction Growing evidence suggests that an individual's style of processing sensory information plays a role in affective disorders. However, most of this work focuses on the relationship between sensory hypersensitivity and factors related to internalizing disorders. This study explores the association between sensory processing styles and impulsivity, a fundamental feature of externalizing disorders, in healthy adults. Method Two hundred and twenty-six healthy individuals aged 18–60 years completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 32 publications
(59 reference statements)
1
27
1
1
Order By: Relevance
“…Such correlates, in autism, include sociocommunicative abilities, insistence on sameness, cognitive problems and inattention, adaptive behavior, and as previously mentioned, anxiety and other forms of affective difficulties [41][42][43][44][45]. Notably, impulsivity is an intrapersonal factor associated with sensation-seeking through NSSI [73] and with acquired capability for suicide [74], and has indeed been linked to self-injurious behavior [75] and to suicidal acts [25] in autistic children. These speculations invite multiple further lines of enquiry, but we are also reminded of the complexity of self-injury and suicidality as interconnected but distinct phenomena.…”
Section: Discussionmentioning
confidence: 90%
“…Such correlates, in autism, include sociocommunicative abilities, insistence on sameness, cognitive problems and inattention, adaptive behavior, and as previously mentioned, anxiety and other forms of affective difficulties [41][42][43][44][45]. Notably, impulsivity is an intrapersonal factor associated with sensation-seeking through NSSI [73] and with acquired capability for suicide [74], and has indeed been linked to self-injurious behavior [75] and to suicidal acts [25] in autistic children. These speculations invite multiple further lines of enquiry, but we are also reminded of the complexity of self-injury and suicidality as interconnected but distinct phenomena.…”
Section: Discussionmentioning
confidence: 90%
“…These studies all reported AASP scores indicating elevated sensory avoidance and/or sensitivity, very low registration, and diminished sensory seeking, compared to healthy control groups. Additionally, studies of non‐clinical samples (often college students) similarly have shown that elevated AASP scores reflecting sensory avoidance, sensory sensitivity, or low registration, combined with a marked reduction in sensory seeking, are associated with high levels of anxiety symptoms (Engel‐Yeger & Dunn, ; Levit‐Binnun, Szepsenwol, Stern‐Ellran, & Engel‐Yeger, ) impulsivity (Hebert, ) and negative affect (Engel‐Yeger & Dunn, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neuroticism and openness positively predicted sensory processing sensitivity; extraversion was negatively associated with sensory sensitivity among undergraduate students (Listou Grimen & Diseth, 2016). Similarly, Hebert (2015) found that underresponsivity was associated with increased impulsivity, whereas individuals with increased sensitivity are less impulsive. Lastly, sensory sensitivity was associated with better performance on a visual detection task but resulted in higher perceived stress among young adults (Gerstenberg, 2012).…”
Section: Temperament and Personality Characteristicsmentioning
confidence: 90%
“…For example, studies of young adults without conditions show that sensory sensitivity is a person characteristic that is related to shyness (Aron et al, 2005), anxiety (Ahadi & Basharpoor, 2010), neuroticism, physical health problems, and conscientiousness and is negatively associated with extroversion (Listou Grimen & Diseth, 2016). Difficulties with sensory registration (i.e., underresponsiveness) are related to increased impulsivity (Hebert, 2015). In addition, studies suggest that individuals with increased sensory sensitivity are more vulnerable to negative environmental factors, which contributes to and perpetuates behaviors related to anxiety or depression (Aron et al, 2005).…”
Section: Mediation Modelsmentioning
confidence: 99%